Towards an Effective VR System for Training Soccer Athletes - Secco, Otávio; Negrão, Matheus D.; Dietrich, Carlos; Nedel, Luciana (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais do XXVII Simpósio de Realidade Virtual e Aumentada, 2025)
Virtual Reality (VR) is a powerful tool for perceptual-cognitive skills training in sports. In this paper, we present a VR system that reconstructs a real soccer game from 3D motion capture (mocap) data, allowing users to navigate the virtual environment freely – either physically or via controllers – offering a dynamic and untethered training perspective of decision-making and perceptual cognitive skills. We conducted a set of three preliminary user studies with a total of 30 volunteers to identify usability flaws, gather users’ feedback on interaction design and comfort, and refine the application into a stable and intuitive prototype. The iterative validation process conducted by us revealed some usability findings that are described here and shaped the final prototype. Future research will involve testing the refined prototype with professional athletes and coaches to gather expert feedback and formally assess its potential as a training aid.